Confrontando informações de fake news na aula de Biologia - sequência didática sobre a febre amarela - Matheus Felipe Dias Barbosa (2019)
The phenomenon of fake news has become visible worldwide today. It is remarkable the presence nowadays of such falsified versions in newspapers and diverse digital medias. Researchers on the subject point to a "post-truth era" as responsible for the growth of the phenomenon. Fake news in the scientific and medical area has generated social discomfort due to the negative impact on public health. Scientific literacy can be a strategy to combat the emergence of fake news. With the objective of working on curricular contents on Yellow Fever and its prevention, promoting the scientific literacy, the present work presents a current proposal to approach this subject. Taking as a starting point the information presented in fake news, a didactic sequence was developed with investigative approach, in which high school students analyzed different texts to solve a problem: which information is scientific and what is false, misrepresentation and / or scientific misunderstanding. In this didactic sequence, the students were grouped, and the participation in discussions; collectively construction of new knowledge; systematization and challenge of the knowledge was stimulated by demanding text productions and training assessment questions. Attitudinal and procedural learning were observed at all moments of the didactic sequence, through participation, discussions, texts and materials produced. Such learning can contribute to the formation of students with a more investigative, autonomous, skeptical and critical profile. Therefore, may increase the probability to have students less vulnerable and more capable of properly dealing with the fake news phenomenon.